外来がん薬物療法を受ける高齢がん患者のきこえときこえの問題にともなうコミュニケーションの実態 - 池田 香菜子; 田村 沙織; 荒尾 晴惠 (日本がん看護学会誌, 2024)
要　旨　目的：研究目的は，外来がん薬物療法を受ける高齢がん患者のきこえときこえの問題にともなうコミュニケーションの実態を明らかにし，きこえの状態に配慮したコミュニケーションへの示唆を得ることである．　方法：量的記述的研究デザインである．外来がん薬物療法を受ける65歳以上の高齢がん患者を対象に，きこえの状態および医療者とのコミュニケーションについて無記名自記式質問紙と診療録による調査を行った．全項目の記述統計を算出後，きこえの問題の経験の有無で2群に分類し，コミュニケーションの満足度をMann-Whitney U 検定で検討した（有意水準は両側5％）．　結果：対象者127名の平均年齢は74.6±5.2歳，男性76名（59.8％），疾患は肺がん41名（32.3％）が最も多かった．医療者とのコミュニケーションで，きこえの問題を経験した者は68名（53.5％），そのことを医療者に訴えた者は23名（33.8％），きこえの問題により治療や療養生活に影響がある者は25名（36.8％）であった．医療者とのコミュニケーションに満足しているのは71名（55.9％）であり，きこえの問題の経験あり群は経験なし群よりも満足度が有意に低かった（p&<.05）．　考察：医療者とのコミュニケーションで半数を超える者がきこえの問題を経験していたことから，治療開始前に高齢者のきこえの状態を評価する必要がある．また，医療者とのコミュニケーションへの満足度も低かったことから，コミュニケーション方法や環境を改善する必要がある． 　Objectives: To elucidate the state of communication associated with hearing in elderly cancer patients undergoing chemotherapy and to obtain suggestions for communication taking into consideration the state of hearing.　Methods: This is a quantitative, descriptive study. We used an anonymous self-administered questionnaire and surveyed the medical records of elderly patients aged ≥65 years who were receiving chemotherapy on an outpatient basis for their state of hearing and communication with medical staff. After calculating the descriptive statistics of all items, difficulty hearing was classified into two groups, and communication was examined using the Mann-Whitney U test (a two-tailed p value of 0.05 was considered significant).　Results: In the subject sample of 127 patients, the mean age was 74.6 ± 5.2 years, there were 76 men (59.8%), and the most common disease was lung cancer in 41 patients (32.3%). Sixty-eight patients (53.5%) experienced difficulty hearing when communicating with medical staff, 23 patients (33.8%) complained about this to medical staff and 25 patients (36.8%) had difficulty hearing which affected their treatment and care. Furthermore, 71 patients (55.9%) were satisfied with their communication with medical staff, and the level of satisfaction was significantly lower for the group with hearing difficulties than the group without hearing difficulties (p &< 0.05).　Discussion: It is important to evaluate the state of hearing of elderly patients before treatment initiation, as more than half of the patients experienced hearing difficulties in communicating with medical staff. Furthermore, the low level of satisfaction in communicating with medical staff indicates the need to improve communication methods and environment.